Design and manufacture of microreactors for the removal of azo dyes by laccase immobilized on magnetite nanoparticles (2020)
In this work, the manufacture and testing of three different magnetic microreactors based on torus geometries (i.e. one-loop, two-horizontal-loop, and two-vertical-loop) is explored to increase the enzyme-based degradation of dyes by laccase bionanocompounds, improve the particle suspension and promote the interaction of reagents. Laccase enzyme was covalently immobilized on amino-terminated silanized magnetite nanoparticles (Lac-Magnetite) and the pH stability was analyzed. Eriochrome Black T (EBt) was tested as a biodegradation of dyes model at three different concentrations 5 mg/L, 10 mg/L and 20 mg/L. The phenol oxidation/removal was evaluated on artificial wastewater and real wastewater. The optimal performance of the bionanocompound was under pH 4 to 4.5. A parabolic movement on the particles was generated by the magnetic field, breaking the stability of the laminar flow and improving the mix. Based on the simulation and the experimentation with the three geometries, the two-vertical-loop demonstrated a better performance due to a bigger dead zone area and longer residence time. Also, the overall average of dye removal using this microreactor with the Lac-Magnetite treatment were 98.05%, 93.87%, and 92.74% for the three concentrations evaluated. The maximum phenol oxidation on the artificial wastewater was 79.89% with Lac-Magnetite at low concentration and the phenol removal ratio at a large volume real wastewater was 17.86%, which is equivalent to perform 200 work cycles of the biodegradation of dyes process.